Determination of an Effective Organic Baiting Technique in Harvesting of Termites (Macrotermes Bellicosus) for use as Alternative Source of Protein for Poultry. - Haira, Wilson Onyango (JOOUST, 2024)
The aim of this study was to determine the most effective organic baiting technique for the mass harvesting of Macrotermes bellicosus. Existing traditional baiting techniques are neither environmentally sustainable nor suitable for trapping of large quantities of Macrotermes bellicosus. The objective was to determine an optimal technique by experimenting on effects of organic baits and environmental factors on the count of Macrotermes bellicosus. Around two separate mounds, 5 treatments replicated 3 times using earthen pot and plastic containers of maize stocks, eucalyptus stems, lantana camara twigs, Napier grass and rice husks, were set up. A Hobo data logger recorded temperature and humidity on an hourly basis and a count of termites harvested at 6 am and 6 pm over the 21 period was taken. Analysis of Variance (ANOVA) test at p = 0.05 and the Least Significant Difference (LSD) technique were used to test the research hypothesis. The effects of organic baits on termite counts differed significantly (p < 0.05) and maize straws emerged as the most effective bait. Further, environmental factors had a statistically significant effect (p < 0.05) on the mean count of termites. The ideal environmental conditions of high humidity (91.0 %) and low temperatures (22.1 0 C) occur at night and collection at 6.00 am led to the highest mean termite count (2,021). Earthen pots mimicked the ideal environmental conditions for termites with higher mean termite counts (1,987) than plastic containers (774). From the findings the optimal termite baiting technique needs to incorporate both bait preference and environmental factors. Earthen pots with maize straws placed overnight around mounds and emptied at 6 am is the recommended organic baiting technique for the mass harvesting of Macrotermes bellicosus. These findings may have practical, policy and theoretical implications for research on the role of termites in sustainable agriculture.
Keywords: Bait preference; mass trapping; Macrotermes bellicosus